POGO travel journal: Komfo Anokye Teaching Hospital (KATH) in Kumasi, Ghana - R. Carter Clement, MD, MBA; Jeffrey B. Peck, MD; Stephen E. Adolfsen, MD (Elsevier, 2024)
This report describes the travels of three members of the Pediatric Orthopaedic Society of North America (POSNA) Pediatric Orthopaedic Global Outreach (POGO) Committee to Komfo Anokye Teaching Hospital (KATH) in Kumasi, Ghana in May, 2023. The trip was coordinated in partnership with Health Volunteers Overseas (HVO). Daily activities included both clinical involvement and pediatric Orthopaedic education for local trainees. This report also describes relevant aspects of the KATH Orthopedic Department with an emphasis on their pediatric Orthopaedic services. Finally, the authors provide reflections that may be helpful for future visitors to KATH or elsewhere.